(untitled) - Schwartz, Randal L. (Sebastopol, California, 1997)
Learning Perl is a hands-on tutorial designed to get you writing useful Perl scripts as quickly as possible. Exercises (with complete solutions) accompany each chapter. A lengthy new chapter in this edition introduces you to CGI programming, while touching also on the use of library modules, references, and Perl's object-oriented constructs.
Keywords: Perl ( computer program language )